1997
DOI: 10.3758/bf03199052
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stimulus attributes on duration matching-to-sample in pigeons

Abstract: A duration matching-to-sample procedure was used to examine the influence of signal properties on temporal estimation and working memory. The results indicated that pigeons responded to durations of a light as if they were longer than equal durations of the absence of the same light, but delay performances did not differ between the two sample types. Similarly, pigeons responded to durations of a bright white light as if they were longer than equal durations of a dim red light, but again, delay performances di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
22
2
Order By: Relevance
“…However, it was also noted that empirical findings have often differed from that theoretical figure (Kraemer et al, 1995;Kraemer et al, 1997). It was suggested earlier that a better estimate of the unbiased effect of the manipulation represented by the present study would be the mean of the 4-sec choose-short effect and 8-sec choose-long effect because the expected grouping effect for the two kinds of test trial should be in the opposite direction.…”
Section: Testingmentioning
confidence: 50%
See 1 more Smart Citation
“…However, it was also noted that empirical findings have often differed from that theoretical figure (Kraemer et al, 1995;Kraemer et al, 1997). It was suggested earlier that a better estimate of the unbiased effect of the manipulation represented by the present study would be the mean of the 4-sec choose-short effect and 8-sec choose-long effect because the expected grouping effect for the two kinds of test trial should be in the opposite direction.…”
Section: Testingmentioning
confidence: 50%
“…Although the subjective midpoint of a temporal discrimination is typically close to the geometric mean of the two training durations, some variability has been found when the brightness or hue of the timed stimuli are manipulated (Kraemer, Brown, & Randall, 1995;Kraemer, Randall, & Brown, 1997). If we can assume that whatever deviation from the geometric mean would be similar for the 2-8 sec discrimination and the 4-16 sec discrimination, then the proposed design controls for those deviations because the proposed grouping effects would be expected to bias the pigeons to choose short on 4-sec sample test trials and to choose long on 8-sec sample test trials.…”
mentioning
confidence: 99%
“…However, in most cases, the data are collapsed across the samples because the effect of brightness is not of central interest. To our knowledge, the research that came closest to testing the question of interest here was performed by Kraemer, Randall, and Brown (1997). They used both long and short samples of both a bright white light and a dim red light.…”
mentioning
confidence: 99%
“…Although Mantanus (1981) reported that pigeons' temporal discriminations were more accurate with filled intervals than with empty intervals, the interpretation of this effect is ambiguous because of a number of design and general test procedure problems, which were described by Kraemer, Randall, and Brown (1997). In order to address these concerns, Kraemer et al (1997) conducted a study in which pigeons were trained to discriminate either filled intervals (light present) or empty intervals (light absent). They found that pigeons judged the duration of a filled interval to be longer than that of an empty interval of equivalent physical duration.…”
mentioning
confidence: 99%